Sensuous intoxication: Learning from bodies in organisational ethnography. Issue 4 (September 2022) - McConn-Palfreyman, Will; Mangan, Anita; McInnes, Peter
An increasing number of management articles have focused on embodied ethnography in terms of either understanding other bodies at work or how our own bodies as researchers inform knowledge. In advancing this latter approach, we argue for an embodiment that sensually intoxicates our bodies, enabling new forms of learning to emerge. To grow this understanding, we draw on Maurice Merleau-Ponty's concept 'le schéma corporel', a shared physiognomy of the senses. This concept informs a corporeal methodology which details three organisational depictions that emerge from a season long immersion in a professional rugby team. We illustrate how the Will was corporeally apprenticed in this setting through an understanding of the body as situated, emotional and physical. The article concludes by suggesting it is the researcher's own body that is the site of learning, providing a sense to the reader of the pain, touch and sound of professional rugby.